IMPLEMENTASI SISTEM PENGELOLAAN PENGADUAN TERINTEGRASI BERBASIS CITIZEN RELATIONSHIP MANAGEMENT (CRM) DALAM PENINGKATAN KUALITAS PELAYANAN PUBLIK DI PROVINSI DKI JAKARTA - Dian Malik Puspitasari; Herry Rachmatsyah; Harry Nenobais (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the integrated Citizen Relationship Management (CRM) complaint system in improving public services in the Province of DKI Jakarta. The research was motivated by the increasing need for digital-based public services as part of smart governance implementation through Jakarta Smart City. This study employed a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The analysis used George C. Edward III’s policy implementation theory, which consists of communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of CRM in DKI Jakarta has generally been carried out effectively through the integration of various complaint channels such as the JAKI application, social media, and direct service channels. The system has contributed to improving transparency, responsiveness, and public participation in public service delivery. However, several obstacles remain, including limited human resource capacity, unequal digital literacy among citizens, technical system disruptions, and sectoral ego between government agencies that hinder coordination. Supporting factors include visionary leadership, clear bureaucratic structures, inter-agency communication, and the utilization of information technology. Therefore, strengthening coordination, improving digital infrastructure, and enhancing the capacity of human resources are necessary to optimize the effectiveness of the CRM system in public service delivery in DKI Jakarta.